55.9k views
1 vote
I learned this so long ago & i don’t remember how to do it. plz help

I learned this so long ago & i don’t remember how to do it. plz help-example-1

1 Answer

2 votes

(21)

Suppose, we have to find average rate of change of f(x) on [a,b]

we can use average rate of change formula


A=(f(b)-f(a))/(b-a)

we are given


f(x)=x^2+4x+1


f(4)=4^2+4*4+1


f(4)=33


f(-1)=(-1)^2+4*(-1)+1


f(-1)=-2


A=(f(4)-f(-1))/(4+1)


A=(33-(-2))/(4+1)


A=7.............Answer

(22)

Suppose, we have to find average rate of change of f(x) on [a,b]

we can use average rate of change formula


A=(f(b)-f(a))/(b-a)

on [-2,3]


A=(g(3)-g(-2))/(3+2)

we can look at the table

g(3)=12.5

g(-2)=400

so, we can plug these values


A=(12.5-400)/(3+2)


A=-77.5.........Answer

User Ray Yun
by
5.8k points